Potential germination of commercialized seeds and production of dalia seedlings in Varzea Grande, Mato Grosso, Brazil - Suzelaine Aparecida da Silva Matos; Glauce Portela de Oliveira (Acta Biológica Catarinense, 2020)
There is little information on the cultivation of species with ornamental potential in Mato Grosso. The aim of this work was to evaluate, in Varzea Grande (MT), the favorable environment for the production of Dahlia pinnata Cav. and the quality of the seeds sold for this purpose. The experiment took place at the Seed Laboratory and at the experimental field of Varzea Grande University Center (Univag), Mato Grosso. Seeds of this species were purchased in commercial packaging. The seeded materials were arranged in the greenhouse with 50% shading (Sombrite®) and in full sun, both with daily irrigation. Growth assessment was performed from the seventh day after emergence. The number of emerged plants was evaluated from the first week after sowing until the establishment of seedlings.Analysis of variance was performed by Tukey test at 5% and regression analysis. The germination test showed 71% of normal seedlings, a lower value than the minimum germination described in the package, and emergence and establishment of 32% of the seedlings. The evaluated conditions, in greenhouse under 50% shading, were favorable to the production of Dahlia pinnata, even when commercial seeds presented low germination potential